Urgensi Manajemen Persuratan Dalam Meningkatkan Kinerja Guru Di Sekolah Mis Cendikia Insani Al-Washliyah - M Padeli Wibowo; Rizqi Almaajid; Siti Farimah Azzahro Simatupang; Lia Sumayyah; Tengku Darmansah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The urgency of correspondence management in improving teacher performance at the Mis Cendikia Insani Al Washliyah School is an important aspect that must be considered by school management. Effective mail management includes managing incoming and outgoing mail, as well as systematic well-organized document storage. With good correspondence management, important information can be conveyed in a timely and accurate manner, which ultimately supports improved teacher performance. In this context, efficient correspondence management allows teachers to focus on their main tasks, such as lesson planning, teaching implementation, and student evaluation, without being distracted by administrative problems. The use of information technology in correspondence management can also speed up the communication process and reduce the risk of errors or loss of important documents. This research highlights the importance of training and developing correspondence management skills for administrative staff and teachers at the Mis Cendikia Insani Al Washliyah School. With proper training, teachers and staff can better understand and implement an effective correspondence management system. Apart from that, this research also emphasizes the need for support from school management in providing adequate resources and infrastructure to support this system. Thus, improving correspondence management is expected to create a more organized and conducive work environment, which in turn will have a positive impact on teacher performance. Teachers who have easy and fast access to the necessary information and documents can focus more on professional development and improving the quality of teaching. Therefore, good correspondence management is not only an administrative necessity, but also a key factor in achieving higher educational goals at the Mis Cendikia Insani Al Washliyah School.